(untitled) (LACCEI, 2024)
The objective of this research was to determine the influence of social networks on the brand positioning of the Linda Shoes company in the city of Trujillo, 2022. The research had a quantitative approach, with a non-experimental design methodology of a cross-sectional and correlational type. The finite population consisted of 2134 clients and the sample of 237 clients considering women over 15 years old who reside in Trujillo, manage social networks, and have bought more than 2 times online this year. The instrument used was the Likert scale survey-questionnaire, where Cronbach’s Alpha was obtained for social networks (0.922) and brand positioning (0.964). The results showed a moderate positive relationship with a Spearman Rho (0,505), with a Chi-square coefficient (x²=73.286) and the significance test with a (p .01). It was concluded that social media significantly influence the brand positioning of Linda Shoes in the city of Trujillo.